A Retrospective Evaluation of Secondary Wound Healing for Extraction of the Maxillary First Molar in Dogs. (December 2021) - Bissett, Lana; Niemiec, Brook A.
Oral surgery and exodontia can present challenges in veterinary patients, with a particular area of challenge being extraction and closure of the maxillary first molar (M1) in dogs. This retrospective assessment evaluated patients that had the maxillary first molar extracted with placement of a cruciate suture across the alveolus to achieve partial closure and secure the blood clot. Patients that had teeth extracted adjacent to M1 (maxillary fourth premolar [PM4] or second molar [M2]) were excluded from the study. Three groups of patients were assessed: Group A – at the time of extraction of M1, both the maxillary PM4 and M2 were still present in the oral cavity. Group B – at the time of M1extraction only PM4 or M2 was present, but not both. The tissue was completely intact at the location of the missing tooth. Group C – at the time of M1 extraction neither PM4 or M2 were present, but tissue in these locations was intact. In a three-and-a half-year time period (2015-2018), 179 dogs with 213 solitary M1 extractions were performed. Of these 213 extraction sites, 127 sites (60%) had follow up examination within a two-week postoperative period. Of these 127 sites, 126 (99.2%) appeared appropriately healed without complication. The results of this retrospective evaluation demonstrate that primary closure of a maxillary first molar extraction site may not be required for appropriate soft tissue wound healing in canine patients.